Astronaut handbook - McCarthy, Meghan (New York : Knopf, 2008)
Illustrations and simple text describe how astronauts prepare for their first mission into space and what it is like to live in outer space.
Includes bibliographical references.
Kirkus Review.
2.8
K-3
Keywords: Astronautics -- Juvenile literature; Astronautics; Astronautics